Circus practices and university extension: Facing social inequality during pandemic - Kronbauer, Gláucia Andreza; Magnabosco Martins, Claudia Regina (Guará Journal, 2022)
This text aims to present and discuss the strategies found by the extension project “Circo em Contextos”, in association to the “Central for Support and Integration of Projects and Collective Actions”, from UNICENTRO, Irati, to develop its actions during the period of social distancing due to the pandemic caused by COVID-19. The children were especially affected by the process of social distancing. In a very unique way they were kept away fromhool and restricted their development opportunities. Ac-tions were carried out in an attempt to minimize the effects of pandemic among the most vulnerable populations. Every two weeks, “solidarity banks or hangers” were organized in the suburbs of Irati. Those who had something to donate and/or exchange deposited their products and those who need could pick up the products, only for their own use. Food, personal hygiene and cleaning products, clothes, books, peda-gogical activities and toys were collected and donated. Circo em Contextos produced teaching materials about Circus for donation. From these experiences, we argue that the know-ledge and practices promoted by/in university extension hold the potential for valuable contributions to education and to serve the community, even in times of exception, such as those experienced during the Covid-19 pandemic.